BMP2 Regulation of CXCL12 Cellular, Temporal, and Spatial Expression is Essential During Fracture Repair. (15th June 2015) - Myers, Timothy J; Longobardi, Lara; Willcockson, Helen; Temple, Joseph D; Tagliafierro, Lidia; Ye, Ping; Li, Tieshi; Esposito, Alessandra; Moats‐Staats, Billie M; Spagnoli, Anna
ABSTRACT The cellular and humoral responses that orchestrate fracture healing are still elusive. Here we report that bone morphogenic protein 2 (BMP2)‐dependent fracture healing occurs through a tight control of chemokine C‐X‐C motif‐ligand‐12 (CXCL12) cellular, spatial, and temporal expression. We found that the fracture repair process elicited an early site‐specific response of CXCL12+‐BMP2+ endosteal cells and osteocytes that was not present in unfractured bones and gradually decreased as healing progressed. Absence of a full complement of BMP2 in mesenchyme osteoprogenitors (BMP2cKO/+) prevented healing and led to a dysregulated temporal and cellular upregulation of CXCL12 expression associated with a deranged angiogenic response. Healing was rescued when BMP2cKO/+ mice were systemically treated with AMD3100, an antagonist of CXCR4 and agonist for CXCR7 both receptors for CXCL12. We further found that mesenchymal stromal cells (MSCs), capable of delivering BMP2 at the endosteal site, restored fracture healing when transplanted into BMP2cKO/+ mice by rectifying the CXCL12 expression pattern. Our in vitro studies showed that in isolated endosteal cells, BMP2, while inducing osteoblastic differentiation, stimulated expression of pericyte markers that was coupled with a decrease in CXCL12. Furthermore, in isolated BMP2cKO/cKO endosteal cells, high expression levels of CXCL12 inhibited osteoblastic differentiation that was restored by AMD3100 treatment or coculture with BMP2‐expressing MSCs that led to an upregulation of pericyte markers while decreasing platelet endothelial cell adhesion molecule (PECAM). Taken together, our studies show that following fracture, a CXCL12+‐BMP2+ perivascular cell population is recruited along the endosteum, then a timely increase of BMP2 leads to downregulation of CXCL12 that is essential to determine the fate of the CXCL12+‐BMP2+ to osteogenesis while departing their supportive role to angiogenesis. Our findings have far‐reaching implications for understanding mechanisms regulating the selective recruitment of distinct cells into the repairing niches and the development of novel pharmacological (by targeting BMP2/CXCL12) and cellular (MSCs, endosteal cells) interventions to promote fracture healing. © 2015 American Society for Bone and Mineral Research.